Evaluation of a nutrient-based diet quality index in UK young children and investigation into the diet quality of consumers of formula and infant foods. Issue 10 (2nd November 2015) - Verger, Eric O; Eussen, Simone; Holmes, Bridget A
Abstract: Objective: To adapt and evaluate a nutrient-based diet quality index (PANDiet) for UK young children and to determine the nutritional adequacy of their diets according to consumption of young child formula (YCF) and commercial infant foods (CIF). Design: Content and construct validity of the PANDiet were assessed by studying associations between the PANDiet and its components, energy intake, food intakes, and child and maternal characteristics. Four groups of children were defined according to their intake of YCF and CIF: (i) no consumption; (ii) consumption of YCF; (iii) consumption of CIF; and (iv) consumption of YCF and CIF. Child and maternal characteristics, PANDiet scores and food intakes of these four groups were compared. Setting: Secondary analysis of data from the UK Diet and Nutrition Survey of Infants and Young Children (DNSIYC, 2011). Subjects: Young children ( n 1152) aged 12–18 months. Results: The PANDiet was adapted to the UK based on twenty-five nutrients. A lower PANDiet score was linked to lower intakes of YCF, CIF, vegetables and fruits. Determinants of having a lower score were being older, having siblings and having a younger mother with a lower educational level. Compared with children consuming neither YCF nor CIF, PANDiet scores were higher in children consuming CIF (+1·4), children consuming YCF (+7·2) and children consuming YCF and CIF (+7·8; all P <0·001). Conclusions: The PANDiet is a valid indicator of the nutrient adequacy of the diet of UK young children. Consuming CIF was not found to be associated with lower nutritional adequacy whereas consuming YCF was associated with higher nutritional adequacy.